Analysis of Minimum Service Standards for Inpatient Services at the Teluk Kuantan General Hospital - Winda, Nurfa; Habibie, Dedi Kusuma (QISTINA: Jurnal Multidisiplin Indonesia, 2023)
Teluk Kuantan Regional General Hospital is a type C hospital that provides services, one of which is inpatient care. The background of this research is community dissatisfaction with the services at Teluk Kuantan Hospital and the lack of clean rooms that make patients uncomfortable and complaints about slow service. This study aims to describe and analyze the minimum service standards at Teluk Kuantan Regional General Hospital, Kuantan Singingi Regency and the inhibiting factors from the analysis of service standards. In this study, researchers used 6 indicators to measure service standards by Rahmayanty, namely, service procedures, turnaround time, service costs, service products, facilities and infrastructure, officer competence. This study uses a qualitative method that is descriptive. Location The research was conducted at Teluk Kuantan Hospital, Kuantan Singingi Regency. The results of this study indicate that the standard of inpatient service at the Teluk Kuantan Regional General Hospital is not optimal, but it has been assessed as improving from before, the hospital continues to provide the best with an annual evaluation. It is hoped that inpatient services can continue to improve so as to get patient satisfaction. The inhibiting factor in carrying out the analysis of minimum service standards for inpatient services is the lack of human resources and budget which can affect the lack of maximum service.